Diskon Ganda di Kedai Pempek: Lintasan Pembelajaran menggunakan Konteks Daftar Menu New Math Pempek - Siligar, E.I Pusta; Putri, Ratu Ilma Indra; Zulkardi, Zulkardi; Hapizah, Hapizah (Edumatica : Jurnal Pendidikan Matematika, 2026)
A common mistake students make in understanding the concept of discounting, especially double discounting, is to directly add two percentages without considering the order of application and the change in the basis of subtraction after the first discount. Therefore, learning is needed that can help students overcome these problems. This study aims to develop a learning pathway to understand the concept of discounting through the context of the New Math Pempek menu list by utilizing the Indonesian Realistic Mathematics Education approach. The method used is a design research type validation study consisting of: preliminary design, design experiment, and retrospective analysis. The research subjects were 35 students of MTs. Data were collected through video recordings of the learning process, student worksheets, observation notes of student discussions, and interviews, then analyzed retrospectively. The results showed that the learning trajectory began with students understanding information from the menu, acting as buyers, estimating prices after discounts using a bar model, followed by a discussion of double discounts, and solving problems related to discounts in everyday life. This finding confirms the importance of using cultural contexts and real-life experiences to develop and facilitate students' understanding of mathematical concepts, so that learning becomes more meaningful.